Electricity Consumption and Manufacturing Sector Performance: Evidence from Nigeria - Asaleye, Abiola John; Lawal, Adedoyin Isola; Inegbedion, Henry Egbezien; Oladipo, Adenike Omowumi; Owolabi, Akinyomade O.; Samuel, Olayemi Moses; Igbolekwu, Chisaa Onyekachi (International Journal of Energy Economics and Policy, 2021)
Adequate supply of energy is important for sustainable growth in an economy. The rate of the growth of the Nigeria's electricity development is very slow and not effective compare to other emerging economies; this on the other hands has discouraged production, most especially in the manufacturing sector. In light of this, the study investigates the long-run impact of electricity consumption on manufacturing sector performance proxy by output, employment and capital using Canonical Cointegrating Regression. Evidence from the result in the output equation shows that electricity consumption and credit to manufacturing sector have a negative relationship with output. In the employment equation, consumption in electricity and interest rate have negative effects on employment. In the capital equation, electricity consumption is not statistically significant. In conclusion, effects of electricity consumption as input in the manufacturing sector have not improved the performance in the sector. To improve the situation, the study recommends among others the need to create a framework to promote energy efficiency by maximizing output from the power sector and minimize wastage. Keywords: Electricity consumption; Employment; Output; Capital JEL Classifications: Q4; J2; O1; G1 DOI: https://doi.org/10.32479/ijeep.11399